2004
DOI: 10.1111/j.1365-277x.2004.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietetic guidelines: diet in secondary prevention of cardiovascular disease (first update, June 2003)

Abstract: There is good systematic review evidence that dietary advice to those with coronary heart disease can reduce mortality and morbidity as well as modify some risk factors. Dietary advice that does this most effectively should be prioritized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 76 publications
0
15
0
6
Order By: Relevance
“…Cohort studies and controlled trials of dietary fat and CHD mortality or morbidity were identified by searching the Cochrane Library and examining Cochrane reviews [Hooper et al, 2001[Hooper et al, , 2004a; by keyword searches of article databases using Medline, Embase, SCOPUS, Web of Science and PubMed; by examining the tables, figures and list of references in review articles [Hooper et al, 2004b;Booker and Mann, 2008;Erkkila et al, 2008], systematic reviews [Wang et al, 2006], metaanalyses [Bucher et al, 2002;Brouwer et al, 2004;He et al, 2004;Whelton et al, 2004;Yzebe and Lievre, 2004;Mozaffarian and Rimm, 2006;Jenkins et al, 2008] and original articles; and by searching for papers that had cited relevant cohort and intervention studies. The present review was limited to English language publications.…”
Section: Methodsmentioning
confidence: 99%
“…Cohort studies and controlled trials of dietary fat and CHD mortality or morbidity were identified by searching the Cochrane Library and examining Cochrane reviews [Hooper et al, 2001[Hooper et al, , 2004a; by keyword searches of article databases using Medline, Embase, SCOPUS, Web of Science and PubMed; by examining the tables, figures and list of references in review articles [Hooper et al, 2004b;Booker and Mann, 2008;Erkkila et al, 2008], systematic reviews [Wang et al, 2006], metaanalyses [Bucher et al, 2002;Brouwer et al, 2004;He et al, 2004;Whelton et al, 2004;Yzebe and Lievre, 2004;Mozaffarian and Rimm, 2006;Jenkins et al, 2008] and original articles; and by searching for papers that had cited relevant cohort and intervention studies. The present review was limited to English language publications.…”
Section: Methodsmentioning
confidence: 99%
“…The control of cardiovascular risk factors plays an important role in patients' quality of life and survival rates. The World Health Organization has stated that over three-quarters of all CVD deaths may be avoided with adequate changes in lifestyle, including diet and exercise (2-3). …”
Section: Introductionmentioning
confidence: 99%
“…It is a consensus that the Mediterranean diet is effective and possibly the most appropriate dietary intervention for the prevention and treatment of CVD (2,3,4,5,6). This diet is characterized by a low saturated fat intake in addition to a high consumption of vegetables, fish, and olive oil and a moderate consumption of wine (5).…”
Section: Introductionmentioning
confidence: 99%
“…Healthy lifestyle change can reduce morbidity and premature mortality [4,5]. However, fewer than 25% of U.S. adults have lifestyles that meet dietary or physical activity guidelines [6-8].…”
Section: Introductionmentioning
confidence: 99%